2016
DOI: 10.18280/ijht.340113
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Magnetohydrodynamic Couette-Poiseuille Flow within Porous Plates Filled with Porous Medium in the Presence of a Moving Magnetic Field with Hall and Ion-slip Effects

Abstract: A study on the effects of Hall current, ion-slip and permeability on unsteady Magnetohydrodynamic Couette-Poiseuille flow within porous plates filled with porous medium in the presence of a moving uniform transverse magnetic field which is fixed relative to the moving porous plate is carried out. Flow within the channel is generated due to accelerated movement of the lower plate of the channel along x-axis and by an applied constant pressure gradient acting along x-axis. An exact solution of the governing equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In order to solve Eqs. (18), (19) and (22) under the boundary conditions of (23), we assume that Substituting (25) in Eqs. (18), (19) and (22), we obtain the following differential equations:…”
Section: Concentration Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to solve Eqs. (18), (19) and (22) under the boundary conditions of (23), we assume that Substituting (25) in Eqs. (18), (19) and (22), we obtain the following differential equations:…”
Section: Concentration Equationmentioning
confidence: 99%
“…Tusher Mollah et al [17] described influence of Hall and ion-slip current on unsteady MHD Bingham fluid model flow with suction velocity. Influence of Hall and ion-slip current on unsteady MHD Couette-Poiseuille flow with moving magnetic field has been considered by Sigh et al [18]. Satya Narayana et al [19] investigated the influence of thermal and species diffusion on MHD free convective flow past a permeable plate in the presence of Hall current.…”
Section: Introductionmentioning
confidence: 99%
“…Naroua et al [31] presented an analysis on time-dependent flow of partially ionized gas in the presence of Hall and ion-slip current in a rotating channel with heat source. Singh et al [32] studied combined effect of Hall and ion-slip current on unsteady hydromagnetic Couette-Poiseuille flow in the presence of a moving magnetic field. They found out that both primary and secondary component of fluid velocity decreases with the increase in ion-slip parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, they presented isothermal and streamlines at different aspect ratios waviness, and Darcy-Rayleigh numbers. The influence of Hall current, ion slip and permeability on unsteady MHD Coutte-Poiseuille flow in a porous medium in the presence of moving transverse magnetic field was studied by Singh et al [4]. They reported that in the case of pure fluid regime, suction tends to enhance fluid velocity in both the primary and secondary flow directions while injunction diminishes it.…”
Section: Introductionmentioning
confidence: 99%